IRAM: virus capsid database and analysis resource. (18th July 2019) - Almansour, Iman; Alhagri, Mazen; Alfares, Rahaf; Alshehri, Manal; Bakhashwain, Razan; Maarouf, Ahmed
Abstract: IRAM is an online, open access, comprehensive database and analysis resource for virus capsids. The database includes over 200 000 hierarchically organized capsid-associated nucleotide and amino acid sequences, as well as 193 capsids structures of high resolution (1–5 Å). Each capsid's structure includes a data file for capsid domain (PDB), capsid symmetry unit (PDB) and capsid structure information (PSF); these contain capsid structural information that is necessary to run further computational studies. Physicochemical properties analysis is implemented for calculating capsid total charge at given radii and for calculating charge distributions. This resource includes BLASTn and BLASTp tools, which can be applied to compare nucleotide and amino acid sequences. The diverse functionality of IRAM is valuable to researchers because it integrates different aspects of virus capsids via a user-friendly interface. Such data are critical for studying capsid evolution and patterns of conservation. The IRAM database can also provide initial necessary information for the design of synthetic capsids for various biotechnological applications.